Comparison of Effective Population Size, Rate and Level of Inbreeding and its Potential Impact on Village Chicken Populations of Southern Africa - Zulu, S.G.; Muchadeyi, F.C.; Dzomba , E.F. (International Journal of Poultry Science, 2014)
The term village chicken best describes the scavenging chickens because of the effect of the village socio-economic and biophysical environment on the production and health status of the chicken. These chickens are predominantly farmed in African villages by small holder farmers. The purpose of this study was to compare rates and levels of inbreeding in village (free range) chickens in Southern Africa. In addition the study sought to investigate the major economic traits that could be negatively affected by inbreeding. The study was carried out in 2007 and 2009 by sampling households in five agro-ecological zones (AEZ) in Zimbabwe and three farming regions in South Africa. Data was captured in the form of surveys conducted using pre-tested questionnaires and included farmer socio-demographic information and household chicken flock sizes and composition. Data was also captured on traits that chicken farmers target when selecting or culling the flocks by ranking traits in order of importance, one being most important and eight being the least important. Three parameters i.e. effective population size (Ne), rate of inbreeding (ΔF) and the level of inbreeding (F) were estimated using different mathematical formulas. Statistical analysis of the effect of agro-ecological zone and country on each of the three parameters was done using Generalized Linear Models procedure in SAS. Results showed that Limpopo province of South Africa and AEZ III of Zimbabwe had highest and lowest Ne, respectively. Consequently, Limpopo and AEZ III had the lowest and the highest ΔF respectively. Both effective population size and rate of inbreeding varied significantly (p